Influence of Eucalyptus Shelterbelt on Fodder Crop (Sorghum vulgare) - Sharma, K. K.; Khanna, Pradeep; Gulati, Ajay (Indian Forester, 1996)
In Northern India, use of Eucalyptus as windbreak/shelterbelt is well accepted but questions concerning the economic impact on crop production system requires through investigations. In this study, the influence of Eucalyptus trees on agriculture crop viz., Sorghum vulgare in terms of plant density, crop height and fodder yield were found negative in the vicinity of tree. Gross income from Eucalyptus trees for 100 m tree line estimated to Rs. 2144 for 61.35 trees in east-west and Rs. 2399.87 for 74.68 trees in north-south tree line. It was concluded that growing Eucalyptus on field boundaries under irrigated condition had very little impact on associated Sorghum crop and the crop losses due to tree line are well compensated by the income received out of sale of trees.